Chronicle 104th AES Convention - Jan ADAMCZYK (Archives of Acoustics, 2014)
Again, the 104th Convention held in Anmsterdam in May 1998, gave an opportunity, like the 103rd one in New York, to celebrate the golden anniversary of the first 50 years of the Audio Engineering Society. The site for this European golden gala Covention was very well chosen. Amsterdam, the venerable city, with ancient traditions and precious monuments, created, like it did four years ago, a delighful atmosphere of the truly international friendship and cooperation. Opening ceremonies, as well the special celebration meeting, held on Sunday Evening, May 17, were devoted in particular to memories concerning the AES history and the most spectacular achievements attained by AES officers and contributors. The most significant recent accomplishments were honoured by AES citation awards, presented to deserving contemporaries, during this Sunday meeting. The award presentation was of special interest to the Polish AES Section, as well as, probably, to all Polish acousticians, due to the fact that among eight persons awarded this time was Marianna Sankiewicz, the cofounder of the Polish AES Section and its first chairperson. Mrs Sankiewicz received a Citation Award for her outstanding contribution to European Regional development. It may be added here, that during her Vice-Presidency for AES Central Europe Region, she originated and helped organizing several new AES sections (in Russia, Lithuania, Belarus, Ukraina, Poland), thus enlarging the area of AES influence and augmenting the number of AES members by several hundreds. The moment of award presentation is shown on the enclosed photograph. The AES President Subir Pramanik has just handed the Citation Address to Mrs Sankiewicz, both on the celebration stage, being warmly applauded by the numerous audience. The results of the 104th Convention were as successful as those of the past ones. 126 papers, grouped into sixteen paper-sessions, revealed actual scientific progress in the most important domains of audio-engineering. 14 workshop-presentations gave opportunities to participants for more close and detailed insight into technical subjects connected to particular enginering problems. Many other special-type sessions were organized with accompanying presentations, in particular those prepared for students. Several meetings, social events, technical tours were also arranged in a traditional way as during previous Conventions. 118 paper-preprints were edited prior to debates, and distributed among Convention participants. An very rich exhibition with attendance of 296 leading companies from all over the world, completed the achievements of Organizing Committee of the 104th AES Convention. The truly international character of the Convention activities finds its reflection in the provenience of paper authors. They came from 25 countries, mostly from Europe (18). The highest number of papers was presented by authors from United Kingdom (32), next to them were German authors (25), Dutch ones (16) and those from USA(11). Helas Polish authors participation decreased in comparison to previous European Convention (102nd in Munich) - only four papers were presented in Amsterdam, all of them by authors from Wrocław, who, thereby, are worthy of being laudatorily mentioned.